2002
DOI: 10.11150/kansenshogakuzasshi1970.76.594
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Paragonimiasis Westermanii Complicated with Migrating Subcutaneous Induration and Multiple Involvements in the Liver

Abstract: A 33-year-old female was admitted to a hospital with chief complaints of abdominal pain, fever, cough and migrating subcutaneous induration. She had consumed half-cooked crabs 3 months ago. On admission, a mass in the abdominal wall, pleural effusion, a nodular shadow in the right upper lung on the chest X-ray and multiple low density areas in the liver on CT. Peripheral blood examination disclosed marked eosinophilia (5,300/mm3). Although we failed to detect any parasite eggs in stool, sputum and bronchogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They found that the juvenile worms migrating into the abdominal cavity immediately entered the inner wall of the abdominal cavity. Several cases of early stage paragonimiasis have been reported; the authors described that they present as a subcutaneous induration or mass in the abdominal subcutaneous tissue (23-25). We observed subcutaneous air bubbles at day 30 in the subcutaneous tissues of the abdominal wall or chest wall on CT, and this has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the juvenile worms migrating into the abdominal cavity immediately entered the inner wall of the abdominal cavity. Several cases of early stage paragonimiasis have been reported; the authors described that they present as a subcutaneous induration or mass in the abdominal subcutaneous tissue (23-25). We observed subcutaneous air bubbles at day 30 in the subcutaneous tissues of the abdominal wall or chest wall on CT, and this has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In the review of previously reported CT findings, hepatic paragonimiasis was commonly seen as multiple low attenuating lesions which might be scattered or clustered (3, 7, 13). In two case reports, it manifestated as a single, low attenuating lesion mimicking solid mass and mandated surgical resection (8, 9).…”
Section: Discussionmentioning
confidence: 99%
“…After ingested, juvenile worms of Paragonimus migrate to the lung via tortuous tracks (1). For this reason, although primary site of paragonimiasis is the lung, ectopic infestation can occur in unexpected sites such as the brain, subcutaneous tissue and muscles, omentum and mesentery, retroperitoneum, adrenal glands, ovary, epididymis and liver (1-13). …”
Section: Introductionmentioning
confidence: 99%
“…Several cases of early-stage PW have been reported that have presented as a subcutaneous induration or as a mass in the abdominal subcutaneous tissue [9,12]. Yokogawa [3] investigated the migratory route of juvenile PW in cats and rats.…”
Section: Discussionmentioning
confidence: 99%